Review of the genus Saropogon Loew, 1847 (Diptera: Asilidae) from Russia, Transcaucasia and Central Asia, with description of three new species - Sakhvon, Vital V. (Zootaxa, 2020)
Nine species of the genus Saropogon Loew, 1847 are reviewed. Saropogon aliyevi Sakhvon sp. nov. (Azerbaijan), S. astakhovi Sakhvon sp. nov. (Armenia) and S. tajikistanensis Sakhvon sp. nov. (Tajikistan) are described and illustrated. The distribution of some species is increased. Saropogon pittoproctus Loew, 1873 is recorded from Russia (Kalmykia) for the first time. Records of prey of some of the Saropogon species are presented. An identification key to males of the species is given.